Effectiveness of Model Drawing Approach (MDA) in Enhancing the Problem-Solving Skills of Grade 9 Learners - Copia, Shiela Marie B.; Tamban, Victoria E.; Sapin, Sherwin B.; Yazon, Alberto D.; Manaig, Karen A. (Faculty of Teacher Training and Education, Universitas Terbuka, 2024)
The purpose of this study was to evaluate how effective a Drawing Model Approach was at improving the problem-solving skills of Grade 9 students of Palo Alto Integrated School. It; sought to answer if the said approach could enhance the skills of students, specifically in problem identification and solving. In; year 2018 National Achievement Test (NAT), result revealed that studentsÃ¢â‚¬â„¢ score compared to the previous year indicating only a Mean of 0.51 which can still be classified as Ã¢â‚¬Å“low masteryÃ¢â‚¬Â level in the said examination (Albano, 2019). International test results in the Trends in International Math and Sciences Study (TIMSS), showed a gloomy poor performance of Filipino students in the said subject. Out of 45 countries who participated in the conference, the Philippines ranked at the lowest places- 41st in Math and 42nd in Science, respectively (Torres, et al., 2020). Similarly; report of Programme for International Student Assessment (PISA) in 2018 coming from the website of Organization for Economic Co-operation and Development (OECD), showed the Filipino students left behind in terms of performance ranking in areas of Reading, Science and Math compares with its 79 counterpartsÃ¢â‚¬â„¢ nations. In result, Sec. Briones promoted an immediate order to review the countryÃ¢â‚¬â„¢s basic education curriculum to identify the root cause of the problem and what key areas of intervention must be placed accordingly (Luz, 2018). Utilizing quasi-experimental research design, the study involved a total of 25 pairs of students from the experimental and comparison group selected based on the result of the pre-test; from the population of 88 students in the two sections of Grade 9, namely Carnation and Hyacinth. Participants; were randomly assigned either to the experimental group or to the control. The; statistical tools used in this study were mean, standard deviation, independent t-test, and CohenÃ¢â‚¬â„¢s d. Paired; t-test measured the significant difference between the pre-test; and post-test scores. The results of a pre- and post-test mean scores revealed a highly significant difference between the examined mean scores. The learners' post-test means scores performance, as well as the learners' pre-test and post-test mean scores performance, all indicated rejection of the null hypotheses. The group of participants who used the Drawing Model Approach also performed much better in terms of score than the control group. Using this approach, it develops studentÃ¢â‚¬â„¢s critical and creative thinking skills enabling him to solve problem with ease and confidence. Moreover, through this approach, it helps students to visualize the problem by means of representation, essentially builds a scaffolding between relationship of sets of questions (Marsha, 2008), creating a more concrete comprehension of the problem rather than solving it directly within their minds which sometimes create long confusion of array of thoughts. The researcher, through this paper, aimed to contribute to the body of knowledge in making Math subject more interesting by means of simple and effective pedagogical approach to help improve the critical and analytical thinking skills of the students which have been their waterloo based on the poor academic performance on Math for the last three years. Hence, this condition should already address considering on the current situation now which the education of the learners is at stake. Keywords Ã¢â‚¬â€œ Model Drawing Approach, Visualization, Problem-solving skills, Effectiveness, Teaching Style